2017
DOI: 10.1371/journal.pone.0188923
|View full text |Cite
|
Sign up to set email alerts
|

Development of a GAL4-VP16/UAS trans-activation system for tissue specific expression in Medicago truncatula

Abstract: Promoters with tissue-specific activity are very useful to address cell-autonomous and non cell autonomous functions of candidate genes. Although this strategy is widely used in Arabidopsis thaliana, its use to study tissue-specific regulation of root symbiotic interactions in legumes has only started recently. Moreover, using tissue specific promoter activity to drive a GAL4-VP16 chimeric transcription factor that can bind short upstream activation sequences (UAS) is an efficient way to target and enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…First, we chose a list of molecular markers based on their tissular expression in Arabidopsis thaliana : two endodermal markers (WOL, SCR1), one cortical markers (PEP) and one epidermal marker (EXP7) (Sbabou et al ., 2010; Marquès-Bueno et al ., 2016; Sevin-Pujol et al ., 2017). Orthologous lupin genes were found by comparing Arabidopsis protein sequences with all the cDNA-deduced protein sequences of WL genome.…”
Section: Resultsmentioning
confidence: 99%
“…First, we chose a list of molecular markers based on their tissular expression in Arabidopsis thaliana : two endodermal markers (WOL, SCR1), one cortical markers (PEP) and one epidermal marker (EXP7) (Sbabou et al ., 2010; Marquès-Bueno et al ., 2016; Sevin-Pujol et al ., 2017). Orthologous lupin genes were found by comparing Arabidopsis protein sequences with all the cDNA-deduced protein sequences of WL genome.…”
Section: Resultsmentioning
confidence: 99%
“…Although binding to some basic transcription factors, histone acetyltransferases, and the SWI/SNF complex is a common feature of transcriptional activators, the TAD of VP16 is highly efficient and widely used. After replacing the TAD of the host transcriptional activator with the TAD of VP16, the transcriptional activation ability of the activator was significantly improved, which provides a new method for improving the activation efficiency of inefficient transcriptional activators (Langlois et al, 2008;Sevin-Pujol et al, 2017;Mittal et al, 2018;Wang et al, 2019).…”
Section: Vp16 Activates Ie Gene Transcription Via Its Tadmentioning
confidence: 99%
“…In the late stage, VP16 assembles into the tegument to participate in the assembly of virions and promote their maturation (Jonker et al, 2005b;Zhang et al, 2016). In recent years, research on VP16 has found that its function is powerful and involves complex regulatory networks (Zhang et al, 2016;Sevin-Pujol et al, 2017). This article will explain the role of VP16 in promoting IE gene transcription, as well as its role in viral assembly and how VP16 functions when the virus reactivates from latency, providing new insights into the maturation of alphaherpesviruses and the role of VP16 in the viral life cycle.…”
Section: Introductionmentioning
confidence: 95%
“…An example of this approach is the use of the Drosophila ENGRAILED homeodomain to impart repressor function to the transcription factors, thereby creating loss-of-function phenotypes in both invertebrate and mammalian models (Badiani et al, 1994; John et al, 1995; Tolkunova et al, 1998; Chandler and Werr, 2003). Conversely, transgene constructs comprising viral activator domains such as VP16 from herpes simplex virus can activate target genes when fused to GAL-4 (Sevin-Pujol et al, 2017). The specific gene targeting capabilities of nucleoproteins comprising an inactive form of the Cas9 endonuclease, dCas9, and gRNAs can also be harnessed to tether repressor domains such as KRAB or activators such as VP64 to precise genome loci to achieve transcriptional repression (CRISPRi) or activation (CRISPRa) of target genes (Dominguez et al, 2016).…”
Section: Future Directions In the Use Of Dominant Transgene Constructmentioning
confidence: 99%